2019
DOI: 10.1200/jco.2019.37.15_suppl.e12592
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of circulating cytokines in breast cancer: A prospective study in sixty breast cancer patients in Tunisia.

Abstract: e12592 Background: Breast cancer is the second most common cancer and the fifth most common cause of cancer mortality worldwide. The functional relationship between inflammation and cancer is an old concept of cancero- genesis, and it is now clear that inflammatory process certainly potentiates and/or promotes neoplastic risk. However, many of the molecular and cellular mechanisms mediating this relationship remain unresolved. The aim of this study is to measure the level of circulating cytokines (IL17, IL6, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The results in the study that demonstrated the higher significantly difference (P<0.01) levels of IL-22 with tumor grades in patients of breast cancer. The results agreed with study in Tunisia, found the high level of IL-22 was significantly associated with a high histopathological grade (Grade III) (47). Some recent studies have indicated elevated IL-22 level was correlated with breast cancer progression (28).…”
Section: Discussionsupporting
confidence: 91%
“…The results in the study that demonstrated the higher significantly difference (P<0.01) levels of IL-22 with tumor grades in patients of breast cancer. The results agreed with study in Tunisia, found the high level of IL-22 was significantly associated with a high histopathological grade (Grade III) (47). Some recent studies have indicated elevated IL-22 level was correlated with breast cancer progression (28).…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that chronic inflammation is often present in primary cancers and is associated with proinflammatory cytokines including IL6 and IL17 (36). High levels of the cytokines IL6 and IL17 are also present in the sera of women with breast cancer (37,38), thus placing them in the position to potentially promote chronic inflammation in the contralateral breast. Although speculative, if this supposition is correct it would suggest an important example of the ability of a primary breast cancer to influence the biology of the opposite breast.…”
Section: Discussionmentioning
confidence: 99%